A method for preparing a nitrate sustained-release film for a lithium metal negative electrode

By using nitrate sustained release film in lithium batteries, the problems of metal lithium interface instability and lithium dendrites are solved, and the higher circulation and safety performance of lithium batteries are achieved.

CN119764312APending Publication Date: 2025-04-04JIANGXI GANFENG BATTERY TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411934380.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively inhibit the growth of lithium dendrites and enhance the circulation and safety performance of lithium batteries. The instability of the metal lithium interface leads to excessive consumption of electrolyte.

Method used

A nitrate sustained-release film preparation method is adopted to form a uniformly dispersed slurry by mixing nitrate, polymer and inorganic nanoparticles, scraping it onto the substrate and drying it after obtaining a nitrate sustained-release film, which is used to cover the metal lithium negative electrode.

Benefits of technology

The continuous and stable release of NO3- through the nitrate sustained release membrane regulates the uniform deposition of lithium, inhibits the formation of lithium dendrites, and significantly improves the cycling and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764312A_ABST
    Figure CN119764312A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a nitrate slow-release film for a lithium metal negative electrode, comprising the following steps: step one: adding dried nitrate to an organic solvent, stirring to obtain a clear and transparent solution, step two: adding polymer powder to the clear solution of step one, stirring to obtain a uniformly dispersed transparent glue solution, step three: adding inorganic nanoparticles to the glue solution of step two, stirring to obtain a uniformly dispersed polymer nitrate inorganic nanoparticle slurry, and step four: scraping the polymer nitrate inorganic nanoparticle glue solution obtained in step three onto a substrate, and drying to obtain a nitrate slow-release film; the nitrate slow-release film continuously and stably releases NO3- during a circulation process, and the SEI layer generated by NO3- is preferentially reduced, thereby regulating the uniform deposition of lithium, inhibiting the formation of lithium dendrites, and improving the coulombic efficiency of the battery during the circulation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a method for preparing a nitrate sustained-release membrane for a lithium metal negative electrode. Background Art

[0002] At present, the negative electrode material of commercial lithium batteries is graphite negative electrode, and its theoretical capacity is 372 mAh / g, ​​which cannot meet the market's growing demand for high energy density of lithium batteries. Lithium metal negative has advantages such as ultra-high theoretical specific capacity (3860 mAh / g) and lowest standard potential (-3.04 V vs. SHE), low density (0.534 g / cm3), and the energy density of lithium batteries equipped with metal lithium negative electrode can easily exceed 400Wh / kg. However, metal lithium negative electrode also has problems such as lithium dendrite growth caused by uneven deposition, electrolyte consumption caused by repeated rupture and recombination of SEI, and large volume effect. These problems seriously hinder the commercial application of metal lithium negative electrode. At present, the coping strategies for the problems of metal lithium negative electrode are mainly focused on matching solid electrolytes, using lithium-philic three-dimensional current collectors, electrolyte additives, etc., but these methods will always face the problem of unstable metal lithium interface.

[0003] Currently, many studies are devoted to introducing specific functional additives into the electrolyte, such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), 2-methylfuran (2Me-F), and several alkali metal cations, etc. The purpose is to form a new protective layer, thereby enhancing the solid electrolyte interface (SEI) film on the surface of metallic lithium and improving the cycle stability of the battery.

[0004] However, these protective layers generated by in-situ reactions have some defects. Their mechanical strength is insufficient and the coverage of metallic lithium is not comprehensive. They cannot effectively prevent the rupture and continuous reconstruction of the SEI film caused by the change of metallic lithium morphology during lithium deposition and dissolution. Therefore, it has become an urgent task to develop and apply effective metallic lithium interface layer technology to inhibit lithium dendrite growth, enhance the cycle performance of batteries, improve Coulombic efficiency and improve safety.

[0005] Therefore, the present application provides a method for preparing a nitrate sustained-release film for a lithium metal negative electrode to solve the problems existing in the prior art. Summary of the invention

[0006] The purpose and effect of the present invention are achieved by the following specific technical means: A method for preparing a nitrate sustained-release film for a lithium metal negative electrode, comprising the following steps: Step 1: Add the dried nitrate into an organic solvent and stir to obtain a clear and transparent solution; Step 2: Add polymer powder to the clear solution of step 1 and stir to obtain a uniformly dispersed transparent adhesive solution; Step 3: adding inorganic nanoparticles to the glue solution of step 2, and stirring to obtain a uniformly dispersed polymer nitrate inorganic nanoparticle slurry; Step 4: Scrape the polymer nitrate inorganic nanoparticle glue obtained in step 3 onto the substrate, and obtain a nitrate sustained-release film after drying.

[0007] Preferably, the organic solvent in step 1 is a combination of one or more of NMP, DMSO, THF and DME.

[0008] Preferably, the general chemical formula of the nitrate in step 1 is Xm(NO3)n, wherein X is any one of Li, Ag, Na, K, Mg, Zn, and NH4.

[0009] Preferably, the polymer in step 2 is a combination of one or more of PVDF-HFP, PAN, PEO, PVA, and PTFE.

[0010] Preferably, in step 2, the mass ratio of the polymer to the nitrate is 10:1 or 1:10.

[0011] Preferably, the inorganic nanoparticles in step three include one or more combinations of silicon oxide, titanium oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, iron oxide, barium titanate, lead titanate, lithium nitride, lithium fluoride, lithium aluminate, and montmorillonite.

[0012] Preferably, the particle size of the inorganic nanoparticles in step three is 100-1000 nm.

[0013] Preferably, in step three, the mass proportion of the inorganic nanoparticles in the sustained-release membrane is 0-30%.

[0014] Preferably, the thickness of the nitrate sustained-release membrane in step three is 1-50 um.

[0015] Beneficial effects of the present invention: (1) The present invention realizes the continuous and stable release of NO3- through the nitrate slow-release membrane during the cycle process, and NO3- preferentially reduces the generated SEI layer, thereby regulating the uniform deposition of lithium, inhibiting the formation of lithium dendrites, and improving the coulombic efficiency of the battery during the cycle process; (2) The presence of inorganic particles greatly enhances the mechanical properties of the composite protective film, thereby inhibiting the growth of lithium dendrites and significantly improving the cycle performance and safety performance of the battery; (3) The preparation method of the composite negative electrode of nitrate sustained-release membrane and metallic lithium proposed in the present invention has the advantages of simple process, excellent performance and mass production, and has good application prospects in the industrial production of high-performance lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The present invention is a flow chart for preparing the slurry.

[0017] Figure 2 This is the SEM image of PVDF-HFP@LiNO3 sustained-release membrane.

[0018] Figure 3 This is the distribution diagram of F, O, and N elements in PVDF-HFP@LiNO3 sustained-release membrane.

[0019] Figure 4 This is a diagram of the rolling process of the double-roller machine.

[0020] Figure 5 It is the cycle performance diagram of Example 1 and the control group. DETAILED DESCRIPTION

[0021] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail in the specific embodiments. The following embodiments are only examples of implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the scope of the present invention are all within the scope of patent protection of the present invention.

[0022] according to Figure 1 The stirring process shown above obtains a uniformly dispersed polymer / nitrate / inorganic nanoparticle / organic solvent slurry with a solid content ranging from 7.5% to 15%.

[0023] Will Figure 1 The prepared slurry was evenly coated on a glass plate using a wire rod, and then dried in a forced air drying oven at 80° C. for 1 h. After drying, the film was peeled off from the glass plate to obtain a nitrate sustained-release film.

[0024] Figure 2 This is the SEM image of the nitrate sustained-release membrane. As shown in the figure, the PVDF-HFP@LiNO3 sustained-release membrane has a microscopic pore structure with a pore size of 1~4μm.

[0025] Figure 3 This is the distribution diagram of F, O, and N elements in the PVDF-HFP@LiNO3 sustained-release membrane. As shown in the figure, LiNO3 is evenly distributed in the sustained-release membrane.

[0026] Figure 4It is the composite process of PVDF-HFP@LiNO3 sustained-release membrane and metal lithium belt, 1-active roller 1, 2-upper PET film, 3- PVDF-HFP@LiNO3 sustained-release membrane, 4-lithium belt, 5-lower PET film, 6-active roller 2; according to Figure 4 As shown, the PET film-lithium tape-slow-release film-PET film are stacked in sequence and then sent to a roller machine for rolling. After rolling, the outer two layers of PET film are peeled off to obtain a composite metal lithium negative electrode composited with a nitrate slow-release film. Example 1

[0027] This example is used to illustrate the PVDF-HFP@LiNO3 sustained-release membrane and its application disclosed in the present invention, and includes the following steps: 1. Preparation of PVDF-HFP@LiNO3 sustained-release membrane.

[0028] like Figure 1 As shown, (1) lithium nitrate (LiNO3) and dimethyl sulfoxide (DMSO) are stirred until LiNO3 is completely dissolved; (2) PVDF-HFP is added and stirred to obtain a uniformly dispersed adhesive solution; (3) the adhesive solution is evenly scraped onto a glass plate, and then placed in a forced air drying oven at 80°C for 1 h; (4) the glass plate is taken out and cooled to room temperature, and the adhesive film is peeled off from the glass plate to obtain a PVDF-HFP@LiNO3 sustained-release membrane, in which the mass ratio of PVDF-HFP to LiNO3 is 5:1.

[0029] 2. Preparation of PVDF-HFP@LiNO3 / Li composite lithium metal anode (1) The metal lithium strip, PET film, and PVDF-HFP@LiNO3 film are stacked in the order of PET film-lithium strip-PVDF-HFP@LiNO3 film-PET film, and then sent to a roller machine for rolling; (2) The outermost two layers of PET film are peeled off to obtain a composite metal lithium negative electrode composited with a nitrate sustained-release film.

[0030] 3. Assembly and testing of laminated small soft packages.

[0031] A mixture of 200 g of positive electrode active material lithium nickel cobalt manganese oxide (NCM), 5.3 g of binder polyvinylidene fluoride (PVDF), and 5.3 g of conductive agent acetylene black was added to 140 g of N-methyl-2-pyrrolidone (NMP), and then stirred in a vacuum mixer to form a uniform positive electrode slurry. The slurry was evenly coated on a 16 μm thick aluminum foil, and the coating surface density was controlled to be 39.8 g / cm2. Then, it was dried at 120°C to obtain a positive electrode sheet.

[0032] The composite negative electrode sheet, positive electrode sheet and separator prepared above are alternately stacked in a "Z" shape, the positive electrode tab is ultrasonically welded to the aluminum sheet, and the negative electrode tab is ultrasonically welded to the nickel-plated copper, and then pre-sealed with an aluminum-plastic film, and then the electrolyte (ethylene carbonate: methyl ethyl carbonate: diethyl carbonate volume ratio of 1:1:1, containing 1 mole of lithium hexafluorophosphate) is injected into the above battery, and it is formed in a conventional manner to obtain a lithium-ion battery. The control group battery is prepared using the same steps as above, except that the lithium belt does not have a composite PVDF-HFP@LiNO3 membrane.

[0033] The experimental results show that: Figure 5 As shown, the control group has a conventional metal lithium negative electrode with a capacity retention rate of 79.3% after 60 cycles; the experimental group has a negative electrode composited with a PVDF-HFP@LiNO3 sustained-release membrane, and the capacity retention rate after 60 cycles is 97.5%. Example 2

[0034] This example is used to illustrate the PVDF-HFP@LiNO3+SiO2 sustained-release membrane disclosed in the present invention and its application, and includes the following steps: 1. Preparation of PVDF-HFP@LiNO3+SiO2 sustained-release membrane.

[0035] like Figure 1 As shown, (1) lithium nitrate (LiNO3) and dimethyl sulfoxide (DMSO) are stirred until LiNO3 is completely dissolved; (2) PVDF-HFP is added and stirred to obtain a uniformly dispersed glue solution; (3) nano-gas-phase SiO2 powder is added and stirred to obtain a uniformly dispersed slurry; (4) The slurry was evenly scraped onto a glass plate, and then placed in a forced air drying oven and dried at 80 °C for 1 h; (5) The glass plate was taken out and cooled to room temperature, and the adhesive film was peeled off from the glass plate to obtain a PVDF-HFP@LiNO3+SiO2 sustained-release membrane. The mass ratio of PVDF-HFP to LiNO3 in the sustained-release membrane was 5:1, and the mass proportion of nano-gas-phase SiO2 was 10%.

[0036] 2. Preparation of PVDF-HFP@LiNO3+SiO2 / Li composite lithium metal anode (1) The lithium tape, PET film, and PVDF-HFP@LiNO3 film are stacked in the order of PET film-lithium tape-PVDF-HFP@LiNO3+ SiO2 film-PET film, and then sent to a roller machine for rolling; (2) Finally, the outermost two layers of PET film are peeled off to obtain a composite metal lithium negative electrode composited with a nitrate sustained-release film.

[0037] 3. Assembly and testing of laminated small soft packages.

[0038] A mixture of 200 g of positive electrode active material lithium nickel cobalt manganese oxide (NCM), 5.3 g of binder polyvinylidene fluoride (PVDF), and 5.3 g of conductive agent acetylene black was added to 140 g of N-methyl-2-pyrrolidone (NMP), and then stirred in a vacuum mixer to form a uniform positive electrode slurry. The slurry was evenly coated on a 16 μm thick aluminum foil, and the coating surface density was controlled to be 39.8 g / cm2. Then, it was dried at 120°C to obtain a positive electrode sheet.

[0039] The prepared composite negative electrode sheet, positive electrode sheet and separator are alternately stacked in a "Z" shape, the positive electrode tab is ultrasonically welded to the aluminum sheet, and the negative electrode tab is ultrasonically welded to the nickel-plated copper, and then pre-sealed with an aluminum-plastic film, and then the electrolyte (ethylene carbonate: methyl ethyl carbonate: diethyl carbonate volume ratio of 1:1:1, containing 1 mole of lithium hexafluorophosphate) is injected into the above battery, and it is formed in a conventional manner to obtain a lithium-ion battery. The control group battery is prepared using the same steps as above, except that the lithium belt does not have a composite PVDF-HFP@LiNO3+SiO2 film.

[0040] The results of the experiment showed that the control group had a conventional lithium metal negative electrode with a capacity retention rate of 79.3% after 60 cycles; the experimental group had a negative electrode composited with a PVDF-HFP@LiNO3+SiO2 sustained-release membrane, with a capacity retention rate of 98.4% after 60 cycles.

[0041] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a nitrate sustained-release film for a lithium metal negative electrode, characterized in that: The following steps are involved: Step 1: Add the dried nitrate into an organic solvent and stir to obtain a clear and transparent solution; Step 2: Add polymer powder to the clear solution of step 1 and stir to obtain a uniformly dispersed transparent adhesive solution; Step 3: adding inorganic nanoparticles to the glue solution of step 2, and stirring to obtain a uniformly dispersed polymer nitrate inorganic nanoparticle slurry; Step 4: Scrape the polymer nitrate inorganic nanoparticle glue obtained in step 3 onto the substrate, and obtain a nitrate sustained-release film after drying.

2. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: The organic solvent in step 1 is a combination of one or more of NMP, DMSO, THF and DME.

3. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: The general chemical formula of the nitrate in step 1 is Xm(NO3)n, wherein X is any one of Li, Ag, Na, K, Mg, Zn, and NH4.

4. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: The polymer in step 2 is a combination of one or more of PVDF-HFP, PAN, PEO, PVA, and PTFE.

5. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: In the step 2, the mass ratio of the polymer to the nitrate is 10:1 or 1:

10.

6. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: The inorganic nanoparticles in step three include one or more combinations of silicon oxide, titanium oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, iron oxide, barium titanate, lead titanate, lithium nitride, lithium fluoride, lithium aluminate, and montmorillonite.

7. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: In the step 3, the particle size of the inorganic nanoparticles is 100-1000 nm.

8. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: In the step 3, the mass proportion of the inorganic nanoparticles in the sustained-release membrane is 0-30%.

9. The method for preparing a nitrate sustained-release film for a lithium metal negative electrode according to claim 1, characterized in that: The thickness of the nitrate sustained-release membrane in step three is 1-50 um.

Citation Information

Cited By

  • Nitrate-containing ester curing precursor, preparation method thereof and lithium metal solid-state battery

    CN121260899A